Introducing geomorphology a guide to landforms and processes - Harvey, Adrian (Dunedin Academic Press Ltd., 2012)
Harvey, who taught geomorphology courses at the U. of Liverpool, UK, before his retirement, introduces general readers to the science of geomorphology by discussing the topic from the "top down." He details concepts related to spatial and temporal scales and the two main drivers of landform evolution (internal, geologically driven and external, climatically driven forces), then the spatial scale, including global (continents and mountain systems),regional (individual mountain and hill ranges and river basins), local (rivers, hillslopes, beaches, and glaciers),and micro-scales (weathering phenomena and sedimentary details). He ends with chapters on the integration of timescales and landscape evolution and interactions between humans and geomorphology. The volume avoids mathematical treatments and keeps physics and chemistry to a minimum. There is no index.